Essential elements for Radio Frequency Identification (RFID) adoption for industry 4.0 Smart Manufacturing in Context of Technology-Organization-Environment (TOE) Framework – a review - Rafique, Muhammad Zeeshan; Haider, Mustafa; Raheem, Abdul; Mohd Nizam Ab Rahman,; Muhammad Saad Amjad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Automatic identification and data collection provides an ideal basis for Industry 4.0 Smart Manufacturing. The manufacturing sectors, involving a wide spectrum of physical and digital world, are functioning in extremely challenging environment. To optimize production efficiency, the incorporation of automated data collection technologies such as Bar Code and Radio Frequency Identification (RFID) is essential. Both these technologies have a great overlap in terms of industrial applications and no study reviews the existing literature in this regard. Therefore to cope up this matter, a systematic literature review has been conducted in which the technologies have been studied and compared, followed by the detailed discussion under various contexts of Technology-Organization-Environment (TOE) Framework. It has been observed that both these technologies have been employed in various manufacturing domains such as lean manufacturing, inventory management and production planning. However, it has been observed that RFID technology carried technological superiority over Bar Code technology. The systems utilizing the former are highly reliable, exquisitely capable and perform excellent in case of automation. However, issues such as high capital costs and increased level of technical complexity are few dilemmas in case of adopting RFID based systems. In addition to that, the implementation of RFID systems is complemented by certain essential features of TOE framework, which can help to elevate competitiveness and efficiency of an organization regarding tracking and identification of assets and inventory.